Factors Associated with Non-Evidence-Based Overdose Responses among People Who Use Prescription Opioids Non-Medically in Rural Appalachia. (28th January 2023) - Macmadu, Alexandria; Gurka, Kelly K.; Linn, Herbert I.; Smith, Gordon S.; Feinberg, Judith
Abstract: Background: Opioid-related overdose deaths recently accelerated. In response, overdose education and naloxone distribution (OEND) has been implemented widely, though access remains sparse in rural Appalachia. Despite increasing OEND, risk factors for non-evidence-based overdose responses among the training-naïve remain unknown. Methods: We enrolled 169 adults who use prescription opioids non-medically and reside in rural West Virginia (August 2014-March 2015). Participants were interviewed about witnessing overdose (lifetime and prior-year), characteristics of the most recent overdose, responses to the overdose, and OEND acceptability. Logistic regression was used to assess factors associated with non-evidence-based responses to overdose. Results: Among the 73 participants who witnessed an opioid-related overdose, the majority (n = 53, 73%) reported any non-evidence-based responses. Participants were significantly more likely to report a non-evidence-based response when victims were unresponsive (OR = 3.36; 95% CI = 1.07, 10.58). Common evidence-based responses included staying with the victim until help arrived (n = 66, 90%) and calling 911 (n = 63, 86%), while the most common non-evidence-based responses were hitting or slapping the victim (n = 37, 51%) and rubbing the victim with ice or placing them in a cold shower or bath (n = 14, 19%). While most (n = 60, 82%) had never heard of OEND, the majority (n = 69, 95%) were willing to train, particularly those reporting non-evidence-based responses (n = 52, 98%). Conclusions: These findings underscore the need to expand access to OEND in rural communities and indicate OEND is acceptable to training-naïve individuals who use opioids in rural Appalachia. Given the "harm reduction deserts" in the region, approaches to expand OEND should be pursued.